The impact of 2019 novel coronavirus on heart injury: A Systematic review and Meta-analysis - Li, Jing-Wei; Han, Tian-Wen; Woodward, Mark; Anderson, Craig S.; Zhou, Hao; Chen, Yun-Dai; Neal, Bruce (Progress in cardiovascular diseases, 2020)
Evidence about COVID-19 on cardiac injury is inconsistent. We aimed to summarize available data on severity differences in acute cardiac injury and acute cardiac injury with mortality during the COVID-19 outbreak. We performed a systematic literature search across Pubmed, Embase and pre-print from December 1, 2019 to March 27, 2020, to identify all observational studies that reported cardiac specific biomarkers (troponin, creatine kinase–MB fraction, myoglobin, or NT-proBNP) during COVID-19 infection. We extracted data on patient demographics, infection severity, comorbidity history, and biomarkers during COVID-19 infection. Where possible, data were pooled for meta-analysis with standard (SMD) or weighted (WMD) mean difference and corresponding 95% confidence intervals (CI). We included 4189 confirmed COVID-19 infected patients from 28 studies. More severe COVID-19 infection is associated with higher mean troponin (SMD 0.53, 95% CI 0.30 to 0.75, p < 0.001), with a similar trend for creatine kinase–MB, myoglobin, and NT-proBNP. Acute cardiac injury was more frequent in those with severe, compared to milder, disease (risk ratio 5.99, 3.04 to 11.80; p < 0.001). Meta regression suggested that cardiac injury biomarker differences of severity are related to history of hypertension (p = 0.030). Also COVID19-related cardiac injury is associated with higher mortality (summary risk ratio 3.85, 2.13 to 6.96; p < 0.001). hsTnI and NT-proBNP levels increased during the course of hospitalization only in non-survivors. The severity of COVID-19 is associated with acute cardiac injury, and acute cardiac injury is associated with death. Cardiac injury biomarkers mainly increase in non-survivors. This highlights the need to effectively monitor heart health to prevent myocarditis in patients infected with COVID-19. [Display omitted]